Unleashing the Potential of Urban Agroecology to Reach Biodiversity Conservation, Food Security and Climate Resilience - Miguel A. Altieri; Angel Salazar-Rojas; Clara I. Nicholls; Andrea Giacomelli (Agriculture)
Urban agriculture is considered by many scientists and policymakers as a key strategy to build climate change-resilient communities within cities by strengthening food systems, with positive food security, biodiversity, nutrition and health outcomes. The estimated potential of urban agriculture to provide between 15 and 20% of the global food supply can be enhanced by applying agroecological principles and practices that revitalize urban agriculture cropping systems, thus leading to the design of highly diversified, productive and resilient urban farms on a planet in polycrisis. Two pillars are used in agroecology: (a) restoring spatial and temporal crop combinations that deter pests by enhancing biological control with natural enemies, and (b) increasing soil organic matter through green manures, compost and other organic practices that enhance soil fertility and beneficial microorganisms. In addition to technical and environmental obstacles, there are a series of social, economic and political barriers that limit the scaling-up of urban agriculture. For this reason, it is important to launch policies that establish mechanisms for cities to provide incentives for urban agriculture, including access to land, water, seeds and technical knowledge. The creation of producer–consumer networks around markets with solidarity is critical for local equitable food provision and consumption.